AMERIKA SERIKAT DALAM PUSARAN PERANG VIETNAM 1955-1975 - Reyhan, Muhammad Ega; Pertahanan, Diplomasi (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The Vietnam War, also known as Chiến tranh Việt Nam, was one of the most influential wars in the world. This war is also often referred to as Indochina War II which is a war that took place between North Vietnam (Democratic Republic of Vietnam) and South Vietnam (Republic of Vietnam). The Vietnam War is also often associated as a Cold War manipulation between the United States (US) and the Soviet Union. The Vietnam War itself lasted from 1955 to 1975. This research was conducted using the paradigm of Structural Realism (Neo-Realism) and Clausewitz Theory of War, especially regarding the concepts of Trinity of War and Political Objective. The purpose of this study was to find out: 1) What were the factors that caused the United States to interfere in the Vietnam War?; 2) What was America's Role in the Vietnam War?; 3) What was the factor that caused the United States, known as one of the Super Power countries, to lose the Vietnam war?